Print vs. electronic - student information behavior in a fuzzy information universe - Špiranec, Sonja; Banek Zorica, Mihaela; Hebrang Grgić, Ivana (2008)
The information environment students are entering at the beginning of their academic careers becomes more complex and diversified. The continuum in information experience, provided in the print era, has diminished in the electronic age. The identification of patterns in the information preferences and behavior of students that belong to the generation of « digital natives» could be an important indicator of necessary transformations in educational and information policies of universities. This paper provides a contribution to this aim, by defining generic information behavior patterns of the Faculty of Humanities and Social Sciences' students, more precisely, those enrolled in the first and last year of studies. Potential differences between those two groups would indicate a shift of preferences in information choices inherent to a specific student generation. The research data will be derived from surveys, which will focus on questions like the frequency of usage of different services and information types, students familiarity with the existence of specific information services, their perception of the quality particular resources offer etc. The investigation will specifically focus on scenarios for the integration of information resources into e-learning systems. Examination of the mentioned issues and areas could alert educational policies and strategies to issues which can raise the quality of learning experiences. In conclusion and based on survey results, the authors will try to articulate consequences, guidelines and recommendations for information providers, library policy and faculty administration.
Projekt MZOS
Projekt MZOS
ENG